Opto-electronic characterization of starch capped zinc chalcogenides (core-shell) nanocomposites and their application as Schottky device. (20th August 2020) - Deb, Sujata; Kalita, P K; Datta, P
Abstract: Optoelectronic properties of starch capped zinc chalcogenides (ZnO-ZnS and ZnS-ZnO) core-shell nanocomposites are found to be suitable for use in photoconductive devices. An increase in shell thickness can enhance the charge separation that thereby the efficiency. Schottky diodes based on ZnO-ZnS and ZnS-ZnO core–shells nanocomposites exhibit suitable rectifying behaviour in dark. The fundamental device parameters such as barrier height ( ϕ b ), saturation current (Is ) and ideality factor ( β ) are calculated at 300 K (room temperature) from the I–V curve and the effects of the shell thickness on the device performance has thus been investigated. Variation of ideality factor may be attributed to increasing inhomogeneity and interfacial surface defects across the junction. Schottky diodes are also observed as photodetector in response to blue and green LED lights. Responsivity and quantum efficiency of core/shell based Schottky photodiodes are found to be higher than that of core-based Schottky photodiodes.